Prospecção de marcadores microssatélites potenciais para o melhoramento genético de bovinos - Costa, Marco André Paldês da (2012)
Cattle (Bos taurus) represent an important phylogenetic resource for understanding of evolutionary aspects and complex traits. On its genome, microsatellites repeats constituted the basis for genotyping in different studies as the genetic mapping. So, this study has by aim to describe the distribution of these sequences along of the taurine bovine genome, ascribing to them structural and functional annotation, besides supply a resource for that such information may assist future investigations on these regions. With a genomic coverage estimated at 0.8%, around 1.3 million loci were identified, of which 90.5% classified as perfect. Monomers occurred in greater number and frequency, followed by tetramers, dimers, trimers, pentamers and hexamers. However dimers and pentamers contributed in density more than tetramers. Regardless of the type of repetition, always the largest proportion of repetitive stretches distributed on IG, Introns and GPG regions. Nevertheless, density and frequency on PR and 5'UTR overcame IG. Through of these descriptors similarities could be observed between IG, Introns and 3'UTR, as too for PR and 5'UTR. Annotation for biological process, molecular function and cellular component were super-represented in genes harboring repetitive sequences. Using mapping references, as gene annotation, STS, SNPs and other repetitive elements already described, the Pampeano Animal Genetic Resources online platform provides an important resource for that the information gathered can to assist the planning of new approaches, in especial to obtaining molecular markers destinated to selection of traits of interest to the genetic improvement of the species.